Perubahan Iklim dan Dampaknya Terhadap Sistem Perlindungan Anak Pada Masyarakat Tradisional Di Kupang (Nusa Tenggara Timur) dan Palu (Sulawesi Tengah) - Cholid, Sofyan; Pranawati, Santy Yanuar; Rahmawati, Restri (Jurnal Ilmu Kesejahteraan Sosial, 2015)
The Facts about climate change and its impact on the ecosystem across the world has been taking greater attention from scholar, government, scientist, activist, as well as civil community. Based on IPCC report 2007, sea level rise and human development contributed to the lost of coastal wetland and mangroves as well as flooding in coastal areas. This research focused on describing the climate change impacts on children well-being in the society who strongly depend on natural resources, and what kind of the adaptation process and the changing occurred in child protection framework. The methods used include time line, tree problem, ranking activities, and season calendar of important events in both areas. These method were used to document the children development, the important events in which closely linked to changing climate, what kind adaptation they use when problems occurs, how the impacts to their children well being and the way they cope with it. Data showed that children forced to help their parents. The problem perceived in the society that closely linked to climate change and children well being such as food security because the unpredictable weather. They forced to looking for another alternative food supply from rice to cassava, reduce the rice consumption from 3 times a day become once in a day. Second, the impact of climate change exacerbated their economical condition. People forced to seek another job to fulfill their family’s needs. Third, due to their economic condition, it is difficult for them to get the access of education. The school fare was too high for them. The last problem is the lack of information on climate change and adaptation. The intervention from all level include government, NGOs, and civil society to strongly empower the adaptive capacity of indigenous people whose depend on natural resources to cope with climate change is required at least by providing the information.